Relation of Pancreatic Enzymes and Serum Transaminases Levels with Modified CT Severity Index In Acute Pancreatitis (BIRDEM Medical Journal, 2016)
Introduction: Diagnosis of patients with severe acute pancreatitis as soon as possible is critical for achieving optimal outcomes. Management depends largely on severity. Medical treatment of mild acute pancreatitis is relatively straightforward. Treatment of severe acute pancreatitis involves intensive care. Surgical intervention (open or minimally invasive) is indicated in selected cases.Methodology: A total number of 59 subjects were enrolled in this present prospective study in the department of Radiology and Imaging, BIRDEM during two years aim to find out the correlation between CT severity index and patient serum enzyme levels in acute pancreatitis. Patients with clinically suspected and biochemically diagnosed acute pancreatitis referred to Radiology and Imaging department from department of gastroenterology (GHPD), BIRDEM for imaging investigation were enrolled in this study. Severity of acute pancreatitis was measured by both clinical and imaging staging (Modified CT severity index) in mild, moderate and severe groups. Subjects clinical informations and serum enzymes were recorded and analyzed by computer software SPSS (Ver. 20-IBM).Result: Mean age of the study subjects was 36.43 ± 13.85 years. The age ranged from 20-63 years and the maximum number was found in 21 to 40 years age group. Male female ratio was almost 1.56:1. It was seen that diffuse pancreatic enlargement was noted in 20.33% subjects. Pancreatic inflammation with and without peripancreatic fat involvement were observed in 22.72% and 57.62% subjects respectively. Pseudocyst formation (11.86%), ascites (23.72%), renal fascia involvement (37.28%) and pleural effusion (30.5%) were seen in CT scan. The results of the interpreter analysis was Kappa = 0.852 with p < 0.001 when association of severity by clinical scoring and CT severity scoring was compared and revealed that measure of agreement, while statistically significant, was almost perfect agreement. CT severity index in acute pancreatitis had statistically significant (p is less than 0.05) relation with serum amylase (0.738), lipase (0.638), SGOT (0.581) and SGPT (0.365) during admission which was found on simple linear regression test.Conclusion: This present study concluded that modified CT severity index correlated well with patients enzymes level (Amylase, lipase, SGOT, SGPT) as well as clinical findings in acute pancreatitisBirdem Med J 2015; 5(1) Supplement: 18-24